Delayed pneumomediastinum: A rare subacute complication of paraquat poisoning - Gyeltshen, Tashi; Dorji, Kinley Sangay; Nidup (The ASEAN Journal of Radiology, 2021)
Paraquat (PQ) is a non-selective widely used weedicide. Paraquat poisoning has a high mortality rate with no available antidote as of now. It is rare in Bhutan, but mostly discovered in the southern part of the country.Patients usually present with multi-organ failures such as respiratory, liver, and renal failures. This is a case report of a 24-year-old female referred with a history of paraquat ingestion. Initially, she complained of epigastric and retrosternal chestpain with excoriation of the oral mucosa. She later developed acute kidney injury and respiratory distress. Chest CT revealed pneumomediastinum, massive bilateral pneumothoraces, and subcutaneous emphysema. Although there have been few reported cases of pneumomediastinum with or without pneumothorax and subcutaneous emphysema, most of them have an acute presentation (less than 1 week).